2015
DOI: 10.1136/bmjquality.u207936.w3197
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: Improving discharge communication between secondary and primary care

Abstract: Foundation year doctors (FYDs) write most hospital discharge communication, although they have minimal training in this skill. Poor quality discharge summaries increase the risk of adverse events and rehospitalisation. With a multidisciplinary team approach, we developed a list of “golden rules” for good discharge communication. Against these standards, we analysed the quality of electronic inpatient discharge documentation (eIDD) sent over two months from OUH Trust. We found one third of eIDDs were missing de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 7 publications
3
31
0
1
Order By: Relevance
“…The present findings concur with those of Cresswell et al that junior doctors write most hospital discharge notifications, despite receiving little formal teaching on how to do this 12. It was also found that GPs had little understanding of critical illness.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The present findings concur with those of Cresswell et al that junior doctors write most hospital discharge notifications, despite receiving little formal teaching on how to do this 12. It was also found that GPs had little understanding of critical illness.…”
Section: Discussionsupporting
confidence: 89%
“…In line with the experiences of the present study participants, research indicates that hospital discharge summaries are poorly completed and often delayed 10 , 12 , 13 , 2628. Since October 2015, NHS England has required all transfer of care communications to be electronic 29.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Kokeellisen tutkimuksen avulla on osoitettu, että kotiutukseen liittyvät asiat toteutetaan yleisimmin muistinvaraisesti [21]. Potilaiden sairaalasta hoitolaitokseen ja hoitolaitoksesta sairaalaan tapahtuvien siirtotilanteiden parantamiseksi on kehitetty siirtotietoja koskevan informaation tarkastuslistoja [13,[22][23][24]. Tällaiset ns.…”
unclassified